Economic aspects of the commercial breeding of crocodilians - Carreira, Laura Borelli Thomaz [UNESP]; Sabbag, Omar Jorge [UNESP]; Abe, Augusto Shinya [UNESP] (My University, 2017)
The breeding of crocodilians is still a recent activity in Brazil. Its supply chain still requires several adjustments in order to minimize costs and optimize production. Thus, the present study aimed at analyzing the economic feasibility of a commercial farm of Caiman latirostris, identifying of costs in the activity by means of sensitivity analysis, considering the scenarios of average annual revenues of 100% to 10% of sales under a cost of capital of 6% p.y. for the sale of meat and skin combined and separately. The economic result projections for the breeding of this species were positive for an analysis of sensitivity above 30% of combined selling; whereas for the sale of meat or skin separately, the net present value (NPV) was negative to the extent of 50%. For internal rate of return (IRR) the activity is feasible from 30% sale of meat and skin, keeping it unfeasible for scenarios of isolated sale of meat or skin up to 50%. Therefore, the results show that the breeding of Caiman latirostris has economic viability. However, there is a variation between the combined and separate sale of meat and skin for the activity.
Keywords: Alligator; Sensitivity analysis; Viability